Recommendation System Cooperative Stock Goods Orders Using Fuzzy Tsukamoto - Laksa Wibawa, I Made Bagus Wiradivka; Ridwan Satrio, Muhammad; Sri Ariyani, Ni Wayan (International Journal of Engineering and Emerging Technology; Vol 3 No 2 (2018): July - December, 2019)
Various types of daily necessities are available at all-round cooperatives. The Udayana University Karya Bina Sejahtera Civil Servants Cooperative. This cooperative is included as an all-round cooperative that sells various kinds of daily goods and transactions occur every day with considerable intensity. This causes the cooperative to be able to fulfill the demand for goods from the buyer and keep the items sold in good condition. So that in storing the stock of goods must be able to adjust so that the goods are not excessive in inventory or less in the inventory of goods to be sold. Seeing the problems described above, the author feels the need to build a system that can help the cooperative in determining the number of goods ordered. The recommendation system can be built with several methods. One method that can be used is to use the fuzzy logic method. Researchers want to do a study that aims to help in recommending ordering purchases of goods to be ordered based on the number of sales transactions of goods needed from existing data. To make a recommendation for the number of orders for goods, it will be calculated using the Tsukamoto Fuzzy Logic method which is considered suitable to assist in terms of recommending the number of goods purchase orders. With the calculation of this fuzzy logic, the cooperative will later be able to pay attention to the determination of the number of purchase orders for goods so as not to cause excess stock or stock shortages. The development of a system of recommendations for planning stock items can help the cooperative to provide a reference for the number of orders that must be ordered in order to reduce the occurrence of ordering errors as previously explained, such as excess stock or lack of stock